Game Theory Applications in Micro and Macroscopic Simulations in Transportation Networks: A Comprehensive Review - Furkan Ahmad (709809) (2023)
Transportation networks are essential to the functioning of modern societies. They provide access to goods, services, and opportunities, connecting people and places. However, the efficient and effective management of these networks is a complex challenge that requires careful consideration of numerous factors, including capacity, demand, congestion, and user behavior. Game theory (GT) has emerged as a powerful tool for analyzing transportation systems and developing strategies to optimize their performance. This manuscript provides a comprehensive review of the application of GT in transportation networks from both microscopic and macroscopic perspectives. Specifically, it examines how GT has been used to analyze the behavior of individual travelers and transportation providers and how it has been used to develop strategies for managing congestion, improving efficiency, and reducing emissions. Lastly, the manuscript provides a roadmap for future research and highlights the challenges in the application of GT in transportation networks. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2023.3308048